Tumorigenic de-differentiation: the alternative splicing way. (1st November 2020) - Ray, Debleena; Epstein, David M.
ABSTRACT: The mechanism of acquisition of tumorigenic properties by somatic cells at the onset of cancer and later during relapse is a question of paramount importance in cancer biology. We have recently discovered a Muscleblind like-1 (MBNL1)-driven alternative-splicing mediated mechanism of tumorigenic de-differentiation that is associated with poor prognosis, relapse and metastasis in common cancer types.